ROLE OF CATARACT SURGERY IN LOWERING INTRAOCULAR PRESSURE: Lowering Intraocular Pressure - Ahmad, Sabihuddin; Sabih, Ayeza (Pakistan Armed Forces Medical Journal, 2015)
Objective: To study the effects of cataract surgery in lowering of intraocular pressure (IOP).Study Design: Retrospective study.Place and Duration of Study: The Department of Ophthalmology, Combined Military Hospital, Rawalpindi from January 2011 to December 2013.Patients and Methods: The study included a total of 250 patients; of which 100 cases had simple cataract with no coexisting disease, 100 cases had cataract with primary open angle glaucoma and 50 cases of cataract had accompanying pseudoexfoliation glaucoma. All patients were assessed and recorded preoperatively for their IOP, vision, depth of anterior chamber (ACD), angle of anterior chamber by gonioscopy and glaucoma medications being used. Cataract surgery was performed by phacoemulsification and IOL implantations in all cases. These patients were followed up for a period of six months.Results: The intraocular pressure of all these patients was recorded at monthly interval for six months. The IOP showed a significant decrease in all cases and remained constant till the end of the study. A marked improvement of vision was noted in all cases. The depth of the anterior chamber increased and the angle also widened in all cases.Discussion: Cataract surgery has been found to reduce IOP along with improvement in vision. Patients with glaucoma have a dual benefit of reduced IOP and visual improvement after cataract surgery.